MFD (Monetary and Financial Systems Department) Technical Assistance to Recent Post-Conflict Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper reviews the recent experience with technical assistance (TA) to postconflict economies in the monetary and financial areas with a view to providing lessons for ongoing and future work.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet